Naloxone inhibits exercise-induced release of PRL and GH in athletes. - Moretti, C; Fabbri, A; Gnessi, L; Cappa, M; Calzolari, A; Fraioli, F; Grossman, A; Besser, G (1983)
Opiate peptides stimulate the release of GH and PRL, and such changes have also been reported following physical exercise. To investigate opiate involvement in the exercise-induced release of these hormones, eight professional athletes were exercised to 80% of their maximal heart rate on a bicycle ergometer. This exercise alone induced an increase in circulating mean GH (basal to maximal level, 3.1 +/- 0.9 ng/ml-27.3 +/- 5.9 ng/ml) and mean PRL level (6.1 +/- 1.1 ng/ml-19.5 +/- 1.9 ng/ml). Infusion of naloxone (0.3 mg/min) antagonized these responses in mean serum GH (5.6 +/- 1.0 ng/ml to 8.6 +/- 1.1 ng/ml) and PRL levels (6.4 +/- 1.1 ng/ml-8.1 +/- 1.2 ng/ml), which were both significantly less than during the control infusions (P less than 0.01). It is suggested that certain forms of stress stimulate the release of PRL and GH via endogenous opiate peptides.